Selective β2-Adrenoceptor Blockade Rescues Mandibular Growth Retardation in Adolescent Rats Exposed to Chronic Intermittent Hypoxia - Hong, Haixin; Hosomichi, Jun; Maeda, Hideyuki; Ishida, Yuji; Usumi-Fujita, Risa; Yoshida, Ken-ichi; Ono, Takashi (Frontiers in Physiology, 2021)
Activation of the sympathoadrenal system is associated with sleep apnea-related symptoms and metabolic dysfunction induced by chronic intermittent hypoxia (IH). IH can induce hormonal imbalances and growth retardation of the craniofacial bones. However, the relationship between IH and β2-adrenergic receptor signaling in the context of skeletal growth regulation is unclear. This study aimed to investigate the role of β2-adrenergic receptors in IH-induced mandibular growth retardation and bone metabolic alterations. Male 7-week-old Sprague–Dawley rats were subjected to IH for 3 weeks. IH conditions were established using original customized hypoxic chambers; IH was induced at a rate of 20 cycles per hour (oxygen levels changed from 4% to 21% in one cycle) for 8 h per day during the 12-h “lights on” period. The rats received intraperitoneal administration of a β2-adrenergic antagonist (butoxamine) or saline. To exclude dietary effects on general growth, the normoxic rats with saline, normoxic rats with butoxamine, and IH rats with butoxamine were subjected to food restriction to match the body weight gains between IH and other three groups. Body weight, heart rate, blood pressure, and plasma concentrations of leptin, serotonin, and growth hormone were measured. Bone growth and metabolism were evaluated using radiography, microcomputed tomography, and immunohistochemical staining. Plasma leptin levels were significantly increased, whereas that of serotonin and growth hormone were significantly decreased following IH exposure. Leptin levels recovered following butoxamine administration. Butoxamine rescued IH-induced mandibular growth retardation, with alterations in bone mineral density at the condylar head of the mandible. Immunohistochemical analysis revealed significantly lower expression levels of receptor activator of nuclear factor-kappa B ligand (RANKL) in the condylar head of IH-exposed rats. Conversely, recovery of RANKL expression was observed in IH-exposed rats administered with butoxamine. Collectively, our findings suggest that the activation of β2-adrenergic receptors and leptin signaling during growth may be involved in IH-induced skeletal growth retardation of the mandible, which may be mediated by concomitant changes in RANKL expression at the growing condyle.